Network Pharmacology-Based Study on Intervention Mechanism of Lonicerae Japonicae Flos in the Treatment of Alzheimer’s Disease - Chunyan Li, Peng Guo, Xiang Li, Hongmin Wang, Yue Xing, Binbin Guan, Yuyao Hu, Hongxi Lei, Yue Xiaoguan, Qingqing Li, Yunpeng Luan, Li Zheng (Forest Chemicals Review)
The mechanism of Lonicerae Japonicae Flos in the treatment of Alzheimer’s disease was analyzed by network pharmacology. The main active components and targets of Lonicerae Japonicae Flos are screened through TCMSP and online pharmacology database, the gene targets related to Alzheimer’s disease are screened through genome annotation database, the target genes related to AD are screened through human Mendelian genetics (OMIM) database, and the intersection of drug and disease gene targets is obtained by venn diagram package of R language, The main effective components of honeysuckle were screened out for the treatment of Alzheimer’s disease. The gene regulation network of Lonicerae Japonicae Flos for the treatment of AD was drawn by Cytoscape 3.7.2. The visual network diagram of gene protein interaction of honeysuckle was constructed by string database to screen the core genes, the GO and KEGG pathways of the screened gene targets were analyzed by R language. 17 main active components of Lonicerae Japonicae Flos were screened, and 158 gene targets may be involved in the treatment of AD. The results of go and KEGG pathway analysis show that honeysuckle treatment of AD mainly involves biological processes such as cytokine receptor binding, cytokine activity regulation and heme binding, regulating lipid and atherosclerosis, PI3K/Akt, human cytomegalovirus infection, Kaposi sarcoma associated herpesvirus infection Chemical carcinogenesis-receptor activation, hepatitis B, AGE-RAGE and other signaling pathways play a role. Through network pharmacology, the action characteristics of multi active components-multi targets-multi pathways of Lonicerae Japonicae Flos in the treatment of AD were constructed, and the gene targets and signal pathways of honeysuckle in the remedy of AD were comprehensively predicted, which provided a reference for the study of the mechanism of honeysuckle in the remedy of AD.